WEBVTT
00:00:01.760 --> 00:00:08.120
In this video, we will see how to apply differentiation to find an equation of a tangent to a curve at a given point.
00:00:08.320 --> 00:00:17.250
Weβll also discuss what is meant by the normal to a curve at a given point and see examples of how to find the equations of both tangents and normals to curves.
00:00:19.090 --> 00:00:27.530
Weβll recall, first of all, that a tangent to a curve at a particular point is a straight line, which touches the curve at that point but does not cross the curve.
00:00:29.010 --> 00:00:36.640
We will recall also that the gradient or slope of a curve at a given point is defined to be the slope of the tangent to the curve at that point.
00:00:37.090 --> 00:00:54.940
Therefore, it follows that if we can use differentiation to find the gradient function of a curve dπ¦ by dπ₯, then we can evaluate the slope of the curve and hence the slope of the tangent to the curve at a given point by substituting the π₯-value at that point into our gradient function dπ¦ by dπ₯.
00:00:56.290 --> 00:01:05.600
Weβll recall also that the general equation of a straight line with slope π passing through the point π₯ one, π¦ one is π¦ minus π¦ one equals ππ₯ minus π₯ one.
00:01:06.080 --> 00:01:14.610
So we can use the slope, which weβve calculated, and the coordinates of the point at which weβre looking to find the tangent in order to find the equation of a tangent.
00:01:14.940 --> 00:01:17.370
Letβs see how this works in an example.
00:01:19.630 --> 00:01:28.100
Determine the equation of the line tangent to the curve π¦ equals four π₯ cubed minus two π₯ squared plus four at the point negative one, negative two.
00:01:29.110 --> 00:01:31.070
So weβve been given the equation of a curve.
00:01:31.240 --> 00:01:36.310
And we need to determine the equation of the line that is tangent to this curve at a particular point.
00:01:37.380 --> 00:01:43.160
Weβre going to use the formula for the general equation of a straight line π¦ minus π¦ one equals π π₯ minus π₯ one.
00:01:43.590 --> 00:01:46.040
We already know the coordinates π₯ one, π¦ one.
00:01:46.040 --> 00:01:48.440
Itβs the point negative one, negative two.
00:01:48.810 --> 00:01:51.290
But what about π, the slope of this line?
00:01:52.500 --> 00:01:57.920
Well, we recall that the slope of a curve is equal to the slope of the tangent to the curve at that point.
00:01:58.170 --> 00:02:05.420
So in order to find the slope of this tangent, weβre first going to find the gradient function of the curve dπ¦ by dπ₯.
00:02:06.650 --> 00:02:15.730
We can do this by applying the power rule of differentiation, giving dπ¦ by dπ₯ equals four multiplied by three π₯ squared minus two multiplied by two π₯.
00:02:15.860 --> 00:02:18.480
Remember, a constant differentiates to zero.
00:02:18.640 --> 00:02:26.750
So that plus four just differentiates to zero in our derivative, which simplifies to 12π₯ squared minus four π₯.
00:02:26.950 --> 00:02:29.950
Now, thatβs the general gradient function of this curve.
00:02:30.160 --> 00:02:33.060
But we want to know the gradient at a particular point.
00:02:33.230 --> 00:02:40.000
So we need to evaluate dπ¦ by dπ₯ when π₯ is equal to negative one because thatβs our π₯-coordinate at this point.
00:02:41.180 --> 00:02:47.760
This gives 12 multiplied by negative one squared minus four multiplied by negative one, which simplifies to 16.
00:02:48.450 --> 00:02:55.910
We now know that the slope of this tangent is 16 and the coordinates of a point that it passes through are negative one, negative two.
00:02:56.140 --> 00:03:00.900
So we have all the information we need in order to use the formula for the general equation of a straight line.
00:03:02.190 --> 00:03:09.460
Substituting the values of π, π₯ one, and π¦ one gives π¦ minus negative two equals 16 π₯ minus negative one.
00:03:10.540 --> 00:03:13.940
Thatβs π¦ plus two equals 16π₯ plus 16.
00:03:14.760 --> 00:03:20.950
And, then, subtracting two from each side in order to collect the constants gives π¦ equals 16π₯ plus 14.
00:03:22.290 --> 00:03:27.570
So this is the equation of the line tangent to the given curve at the point negative one, negative two.
00:03:27.800 --> 00:03:34.070
It passes through the point negative one, negative two and it has the same gradient as the curve at that point.
00:03:35.210 --> 00:03:37.060
Now, letβs consider a second example.
00:03:39.310 --> 00:03:47.880
Find the point on the curve π¦ equals negative 40π₯ squared plus 40 at which the tangent to the curve is parallel to the π₯-axis.
00:03:48.710 --> 00:03:53.560
Now, letβs think about what it means for a line to be parallel to the π₯-axis.
00:03:54.990 --> 00:03:57.320
The π₯-axis is a horizontal line.
00:03:57.450 --> 00:04:02.530
So if another line is parallel to the π₯-axis, then it must also be a horizontal line.
00:04:02.780 --> 00:04:05.510
And what do we know about the slopes of horizontal lines?
00:04:05.790 --> 00:04:07.480
Well, theyβre equal to zero.
00:04:08.590 --> 00:04:12.940
So we know that the slope of the tangent weβre looking to find must be equal to zero.
00:04:13.480 --> 00:04:18.550
Remember also that the slope of a tangent is equal to the slope of the curve at that point.
00:04:18.760 --> 00:04:23.490
So we also know that the slope of the curve at this point must also be equal to zero.
00:04:24.600 --> 00:04:28.370
The slope of the curve is its gradient function dπ¦ by dπ₯.
00:04:28.550 --> 00:04:37.180
So what weβre going to do is find the gradient function dπ¦ by dπ₯ by differentiating π¦ with respect to π₯ and then set it equal to zero.
00:04:37.540 --> 00:04:44.220
Weβll be able to solve the resulting equation to find the π₯-coordinates of the point on the curve where the gradient is equal to zero.
00:04:45.450 --> 00:04:51.530
Step one then is to find dπ¦ by dπ₯, which we can do by applying the power rule of differentiation.
00:04:51.780 --> 00:04:55.700
It gives negative 40 multiplied by two π₯, which is negative 80π₯.
00:04:55.870 --> 00:04:58.760
And remember, the derivative of a constant is zero.
00:04:58.970 --> 00:05:03.030
So our gradient function dπ¦ by dπ₯ is just negative 80π₯.
00:05:04.220 --> 00:05:08.390
Then, we set dπ¦ by dπ₯ equal to zero and solve the resulting equation.
00:05:08.640 --> 00:05:11.180
We have negative 80π₯ equals zero.
00:05:12.090 --> 00:05:17.200
And by dividing both sides of this equation by negative 80, we find that π₯ is equal to zero.
00:05:17.580 --> 00:05:23.670
So we know that the π₯-coordinate of the point on this curve at which the tangent is parallel to the π₯-axis is zero.
00:05:23.950 --> 00:05:30.460
We also need to find the π¦-coordinate, which we can do by substituting π₯ equals zero back into the equation of the curve.
00:05:31.660 --> 00:05:38.370
When π₯ is equal to zero, π¦ is equal to negative 40 multiplied by zero squared plus 40 which is equal to 40.
00:05:39.440 --> 00:05:46.780
So we find that the point on this curve at which the tangent to the curve is parallel to the π₯-axis is the point with coordinates zero, 40.
00:05:47.600 --> 00:05:54.520
Now, we could also have seen this by considering what the graph of π¦ equals negative 40π₯ squared plus 40 actually looks like.
00:05:55.470 --> 00:06:02.160
Itβs a negative parabola as the coefficient of π₯ squared is negative 40 and it has a π¦-intercept of positive 40.
00:06:02.650 --> 00:06:08.540
We can see from our sketch that this function has a critical point at the point with coordinates zero, 40.
00:06:08.670 --> 00:06:10.560
In fact, itβs a local maximum.
00:06:11.800 --> 00:06:16.390
At the critical points for a function, the gradient of the curve and tangent are equal to zero.
00:06:16.660 --> 00:06:24.600
And so, we see that at the zero, 40 β the critical point of this curve β the tangent at this point will be parallel to the π₯-axis.
00:06:26.580 --> 00:06:28.740
Letβs now consider another example.
00:06:30.750 --> 00:06:38.440
The line π₯ minus π¦ minus three equals zero touches the curve π¦ equals ππ₯ cubed plus ππ₯ squared at one, negative two.
00:06:38.880 --> 00:06:40.180
Find π and π.
00:06:41.450 --> 00:06:47.850
The key information given in this question is that the line and the curve touch at this point with coordinates one, negative two.
00:06:48.160 --> 00:06:56.410
But the line does not cross the curve, which means that the line π₯ minus π¦ minus three equals zero is a tangent to the given curve at this point.
00:06:57.700 --> 00:07:03.220
We know that the gradient of a curve is equal to the gradient of the tangent to the curve at that point.
00:07:04.480 --> 00:07:07.840
The equation of our line is π₯ minus π¦ minus three equals zero.
00:07:08.030 --> 00:07:12.280
And when rearranging, we see that this is equivalent to π¦ equals π₯ minus three.
00:07:13.430 --> 00:07:22.680
Comparing with π¦ equals ππ₯ plus π, thatβs the general form of the equation of a straight line in slope-intercept form, we see that the slope of our tangent is one.
00:07:23.070 --> 00:07:25.590
Can we find an expression for the slope of the curve?
00:07:26.750 --> 00:07:29.010
Well, we can do this by differentiation.
00:07:29.260 --> 00:07:35.910
By applying the power rule, we see that dπ¦ by dπ₯ is equal to three ππ₯ squared plus two ππ₯.
00:07:37.110 --> 00:07:41.200
Next, we evaluate this gradient function at the point one, negative, two.
00:07:41.340 --> 00:07:46.570
So we substitute π₯ equals one into our gradient function, giving three π plus two π.
00:07:47.800 --> 00:07:53.370
We can then equate the gradient of the curve at this point with the gradient of the tangent to the curve at this point.
00:07:53.530 --> 00:07:58.340
And it gives an equation involving π and π: three π plus two π is equal to one.
00:07:59.740 --> 00:08:04.000
We canβt solve this equation because we have only one equation and two unknowns.
00:08:04.200 --> 00:08:06.620
So weβre going to need to find a second equation.
00:08:07.880 --> 00:08:11.490
The point one, negative two lies on both the curve and the tangent.
00:08:11.650 --> 00:08:19.160
So if we substitute the values of one and negative two into the equation of the curve, weβll get a second equation connecting π and π.
00:08:20.280 --> 00:08:28.370
We have π multiplied by one cubed plus π multiplied by one squared is equal to negative two, simplifying to π and π equals negative two.
00:08:29.470 --> 00:08:34.430
We now have two linear equations in π and π, which we need to solve simultaneously.
00:08:35.660 --> 00:08:41.980
We can multiply equation two by two, as this will make the coefficient of π the same as it is in equation one.
00:08:43.100 --> 00:08:48.130
Weβll then subtract the second equation from the first to eliminate the π terms, giving π equals five.
00:08:49.350 --> 00:08:57.130
Substituting this value for π into our original equation two thatβs π and π equals negative two gives five plus π equals negative two.
00:08:57.300 --> 00:09:01.010
And by subtracting five, we see that π is equal to negative seven.
00:09:02.320 --> 00:09:03.920
So we found the values of π and π.
00:09:03.920 --> 00:09:06.830
π is equal to five and π is equal to negative seven.
00:09:07.250 --> 00:09:15.090
A reminder is that the key point that we used in this question is that the slope of a curve is equal to the slope of the tangent to the curve at that point.
00:09:16.410 --> 00:09:18.480
Letβs consider another type of example.
00:09:20.840 --> 00:09:30.990
Find the equation of the tangent to the curve π¦ equals π₯ cubed plus nine π₯ squared plus 26π₯ that makes an angle of 135 degrees with the positive π₯-axis.
00:09:32.350 --> 00:09:39.910
So weβve been asked to find the equation of a tangent to a particular curve, which we know we can do using differentiation and the general equation of a straight line.
00:09:40.280 --> 00:09:46.300
But what does it mean when it says this tangent makes an angle of 135 degrees with the positive π₯-axis?
00:09:46.650 --> 00:09:48.240
Letβs consider a sketch.
00:09:49.200 --> 00:09:50.860
Well, it will look something like this.
00:09:50.860 --> 00:09:52.720
The tangent here is shown in pink.
00:09:52.880 --> 00:10:00.900
And we can see that when intersects with the π₯-axis, the angle between the positive π₯-axis and the tangent is 135 degrees.
00:10:01.910 --> 00:10:13.940
In order to apply the general equation of a straight line π¦ minus π¦ one equals π π₯ minus π₯ one, we either need to know the slope π of our line or the coordinates of a point π₯ one, π¦ one which lies on the line.
00:10:14.310 --> 00:10:22.350
So how does knowing that our tangent makes an angle of 135 degrees with the positive π₯-axis help with determining either of those?
00:10:23.430 --> 00:10:30.880
Well, the angle on the other side of this line will be 45 degrees because we know that angles on a straight line sum to 180 degrees.
00:10:32.110 --> 00:10:38.720
We can sketch in a right-angled triangle below this line and recall that the slope of a line is change in π¦ over change in π₯.
00:10:38.890 --> 00:10:42.660
Thatβs the vertical height of this triangle divided by the horizontal distance.
00:10:44.160 --> 00:10:50.880
But in that right triangle, those sides are the opposite and adjacent in relation to the angle of 45 degrees.
00:10:51.140 --> 00:10:54.810
So weβre dividing the length of the opposite by the length of the adjacent.
00:10:55.170 --> 00:11:01.330
As the line is sloping downwards though, that vertical change is actually the negative of the value of the opposite.
00:11:01.560 --> 00:11:06.070
So we have that the slope is equal to negative opposite over adjacent.
00:11:07.240 --> 00:11:10.340
Opposite divided by adjacent defines the tangent ratio.
00:11:10.560 --> 00:11:14.730
So in fact, this is equal to negative tan of 45 degrees.
00:11:15.610 --> 00:11:18.220
And tan of 45 degrees is just one.
00:11:18.420 --> 00:11:24.080
So by considering this right-angled triangle, we found that the slope of this line is negative one.
00:11:25.310 --> 00:11:27.150
So, we found the slope of our tangent.
00:11:27.150 --> 00:11:31.490
But we donβt yet know the coordinates of the point on the curve where this tangent is being drawn.
00:11:31.870 --> 00:11:37.280
To find this, we need to find the point on the curve where the gradient or slope is equal to negative one.
00:11:38.320 --> 00:11:49.290
We begin by differentiating the equation of the curve with respect to π₯ and applying the power rule of differentiation, giving dπ¦ by dπ₯ equals three π₯ squared plus 18π₯ plus 26.
00:11:50.300 --> 00:11:57.270
We then set this expression equal to negative one to find the π₯-coordinate of the point on the curve, where the gradient is negative one.
00:11:58.420 --> 00:12:02.520
This simplifies to three π₯ squared plus 18π₯ plus 27 equals zero.
00:12:02.700 --> 00:12:07.560
And then dividing through by three gives π₯ squared plus six π₯ plus nine equals zero.
00:12:08.610 --> 00:12:11.340
We should notice that this is, in fact, a perfect square.
00:12:11.430 --> 00:12:14.260
We can write it as π₯ plus three all squared.
00:12:15.360 --> 00:12:19.370
Solving this equation then, this means that π₯ plus three must be equal to zero.
00:12:19.470 --> 00:12:21.760
And so, π₯ is equal to negative three.
00:12:23.150 --> 00:12:30.550
Next, we need to find the value of π¦ when π₯ is equal to negative three, which we do by substituting negative three into the equation of the curve.
00:12:30.750 --> 00:12:32.980
And it gives negative 24.
00:12:34.230 --> 00:12:40.440
We now know that this tangent has a slope of negative one at the point negative three, negative 24.
00:12:40.750 --> 00:12:44.630
All thatβs left is to substitute into the general equation of the straight line.
00:12:45.940 --> 00:12:51.100
π¦ minus negative 24 equals negative one multiplied by π₯ minus negative three.
00:12:52.230 --> 00:12:56.300
That all simplifies to π¦ plus π₯ plus 27 equals zero.
00:12:57.800 --> 00:13:07.180
The key steps in this question then were to use some trigonometric reasoning to identify that if a line makes an angle of 135 degrees with the positive π₯-axis.
00:13:07.500 --> 00:13:13.710
Then, its gradient or slope is equal to negative tan 45 degrees, which is equal to negative one.
00:13:14.180 --> 00:13:20.570
We then use the gradient function of the curve to identify the π₯-value at which the gradient was equal to negative one.
00:13:20.940 --> 00:13:32.890
We found the corresponding π¦-value by substituting into the equation of the curve and then finally used the general equation of a straight line π¦ minus π¦ one equals π π₯ minus π₯ one to find the equation of this tangent.
00:13:34.940 --> 00:13:39.360
Finally, in this video, weβre going to discuss what is meant by a normal to a curve.
00:13:39.570 --> 00:13:42.050
And weβll do this in the context of an example.
00:13:44.240 --> 00:13:52.170
List the equations of the normals to π¦ equals π₯ squared plus two π₯ at the points where the curve meets the line π¦ minus four π₯ equals zero.
00:13:53.740 --> 00:13:56.950
What is meant by the term normal in this context?
00:13:57.310 --> 00:14:02.930
Well, we recall first of all that the tangent to a curve has the same gradient as the curve at that point.
00:14:03.980 --> 00:14:09.850
The normal, however, passes through that same point, but it is perpendicular to the tangent at that point.
00:14:11.200 --> 00:14:19.790
We can use properties of perpendicular lines to deduce the relationship that exists between the gradient of the tangent and the gradient of the normal to a curve at a given point.
00:14:20.070 --> 00:14:26.740
The product of the two gradients will be equal to negative one and they will be negative reciprocals of one another.
00:14:27.140 --> 00:14:34.120
We must make sure that weβre clear whether weβve been asked to find the equation of a tangent or a normal when weβre answering questions like this.
00:14:35.260 --> 00:14:38.990
So now that we know what normals are, letβs see how we can answer this question.
00:14:39.240 --> 00:14:44.810
Weβve been asked to list the equations of the normals to a given curve at the point where this curve meets another line.
00:14:45.020 --> 00:14:48.940
So our first step is going to be to find these points of intersection.
00:14:50.000 --> 00:14:59.230
We can rearrange the equation of the line to give π¦ equals four π₯ and then set the two expressions for π¦ equal to one another to give an equation in π₯ only.
00:15:00.350 --> 00:15:07.760
We can subtract four π₯ from each side and then factor the resulting quadratic to give π₯ multiplied by π₯ minus two is equal to zero.
00:15:08.920 --> 00:15:12.950
The two roots of this equation are π₯ equals zero or π₯ equals two.
00:15:13.140 --> 00:15:16.070
So we know the π₯-coordinates of our points of intersection.
00:15:17.230 --> 00:15:27.350
To find the corresponding π¦-coordinates, we substitute each π₯-value back into the equation of the curve to give π¦ equals zero when π₯ equals zero and π¦ equals eight when π₯ equals two.
00:15:28.480 --> 00:15:30.810
So we now know the two points of intersection.
00:15:30.980 --> 00:15:34.680
And we, therefore, know the coordinates of one point that lies on each normal.
00:15:34.820 --> 00:15:38.290
But we need to determine the gradient or slope of each normal.
00:15:39.310 --> 00:15:46.300
First, we can find the slope of each tangent by differentiating π¦ with respect to π₯, giving dπ¦ by dπ₯ equals two π₯ plus two.
00:15:47.540 --> 00:15:50.170
When π₯ equals zero, the slope will be two.
00:15:50.200 --> 00:15:52.680
And when π₯ equals two, the slope will be six.
00:15:52.860 --> 00:15:56.780
But remember, this is the slope of the tangent, not the slope of the normal.
00:15:57.940 --> 00:16:02.820
To find the slope of each normal, we need to take the negative reciprocal of the slope of each tangent.
00:16:03.020 --> 00:16:08.660
So the slope of our first normal is negative a half and the slope of our second is negative one-sixth.
00:16:09.910 --> 00:16:13.500
Finally, we can apply the formula for the general equation of a straight line.
00:16:14.530 --> 00:16:22.070
For the first normal with a slope of negative a half passing through the point zero, zero, we get the equation two π¦ plus π₯ equals zero.
00:16:23.040 --> 00:16:31.160
And for the second with a slope of negative one-sixth passing through the point two, eight, we get the equation six π¦ plus π₯ minus 50 equals zero.
00:16:32.190 --> 00:16:34.370
So we found the equations of the two normals.
00:16:34.440 --> 00:16:37.140
We must be really careful on questions like this.
00:16:37.320 --> 00:16:40.760
Remember, the slope of the normal is not the same as the slope of the tangent.
00:16:40.890 --> 00:16:47.340
Itβs equal to the negative reciprocal of the slope of the tangent because the two lines are perpendicular to one another.
00:16:49.270 --> 00:16:51.500
Letβs summarize what weβve seen in this video.
00:16:51.900 --> 00:16:58.680
Firstly, we reminded ourselves that the gradient of a curve is equal to the gradient of the tangent to the curve at that point.
00:16:59.830 --> 00:17:07.750
So by differentiating and then substituting the π₯-value at that point, we can find the slope of the tangent to a curve at any given point.
00:17:08.950 --> 00:17:20.500
We can then substitute the slope and the coordinates of the point into the general equation of a straight line π¦ minus π¦ one equals ππ₯ minus π₯ one in order to find the equation of the tangent to the curve at that point.
00:17:21.610 --> 00:17:26.320
We also saw that the normal to a curve is perpendicular to the tangent to the curve at that point.
00:17:26.520 --> 00:17:29.740
And therefore, the product of their slopes is equal to negative one.
00:17:30.910 --> 00:17:37.690
We can apply all of these key results in order to find the equations of tangents and normals to a variety of different curves.